Comparative Efficacy Of Maldi-Tof Ms Versus Conventional Microbiological Methods In Identifying Bacterial Isolates From Puerperal Sepsis - Tony, Kripa; Rai, Yogita; Satija, Sweta; Biswas, Ratna; Jais, Manoj (Journal of Neonatal Surgery, 2025)
Background: Puerperal sepsis, a potentially fatal postpartum infection, continues to be an important cause of maternal morbidity and mortality. The prompt identification of the causal pathogens is vital for successful and timely treatment. While traditional microbiological techniques are the most used, they are limited by both speed and precision. In contrast, MALDI-TOF MS has a faster and more precise method for bacterial identification. This study will contrast these two approaches in the identification of puerperal sepsis patients' bacterial isolates. Methods: his cross-sectional study was done from May 2023 to November 2024 in Lady Hardinge Medical College and Smt. Sucheta Kripalani Hospital, New Delhi. There were 96 puerperal sepsis patients enrolled, for whom blood and high vaginal swab samples were obtained for examination. Conventional microbiological methods as well as MALDI-TOF MS were used for identification of bacteria, and antibiotic resistance was evaluated with the VITEK 2 automated system. Results: The comparison revealed that MALDI-TOF MS and the conventional techniques were in complete agreement in the case of routine pathogens like Escherichia coli and Klebsiella pneumoniae. MALDI-TOF MS, though, gave a more accurate species identification of pathogens like Pseudomonas stutzeri and Enterococcus faecalis, which was identified at the genus level using conventional techniques. High antibiotic resistance was noted, particularly among the gram-negative bacteria. Conclusion: MALDI-TOF MS is a quicker and more accurate bacterial identification method compared to conventional methods, contributing to better management of puerperal sepsis.